2018
DOI: 10.1016/j.joca.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of bone–cartilage interactions in ACL-injured patients with PET–MRI

Abstract: Objective: To investigate changes in bone metabolism by PET, as well as spatial relationships between bone metabolism and MRI quantitative markers of early cartilage degradation, in ACL-reconstructed knees. Design: Both knees of 15 participants with unilateral reconstructed ACL tears and unaffected contralateral knees were scanned using a simultaneous 3.0T PET-MRI system following injection of 18F-sodium fluoride(18F-NaF). The maximum pixel standardized uptake value(SUVmax) in the subchondral bone and the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…also explored correlations between voxel based relaxation time T 1ρ and T 2 in the cartilage with sodium fluoride uptake metrics (slope K i and SUV), showing correlations not only not only in adjacent regions but also in compartments that are not adjoining. Correlations between SUV and cartilage compositional data were also recently shown in ACL subjects …”
Section: Analysis Of Bone Remodelingsupporting
confidence: 57%
See 2 more Smart Citations
“…also explored correlations between voxel based relaxation time T 1ρ and T 2 in the cartilage with sodium fluoride uptake metrics (slope K i and SUV), showing correlations not only not only in adjacent regions but also in compartments that are not adjoining. Correlations between SUV and cartilage compositional data were also recently shown in ACL subjects …”
Section: Analysis Of Bone Remodelingsupporting
confidence: 57%
“…al., 89 whereby repetitive joint loading causes an initial increase in bone remodeling, that is associated with increased vascular invasion of the deep layers of cartilage, which allows access to the cartilage by chondrolytic enzymes unopposed by inhibitors of the degradative proteinases, that cause a breakdown of the extra-cellular matrix, loss of Simultaneous PET-MRI was also recently used to study cartilage and bone interactions. [91][92][93][94][95] Savic et. al.…”
Section: Cartilage-bone Connectomementioning
confidence: 99%
See 1 more Smart Citation
“…In a study of mild to moderate OA patients, increases in cartilage T 1ρ relaxation times, which are associated with a loss of cartilage GAG content, were correlated with increased 18 F‐NaF uptake in the adjoining bone as well as reduced uptake in the nonadjoining compartments . In a separate study of patients with unilateral, reconstructed ACL tears, a correlation was observed between increased 18 F‐NaF uptake measures of bone remodeling and increased T 2 values in adjacent cartilage, which is indicative of early collagen matrix breakdown . This correlation was particularly pronounced in the deep layers of cartilage adjacent to the subchondral bone.…”
Section: Applications Of Pet‐mri In Nononcologic Musculoskeletal Diseasementioning
confidence: 91%
“…c). Furthermore, in patients with unilateral, reconstructed anterior cruciate ligament (ACL) tears within 10 years of their injury, who have a known increased risk for developing accelerated OA, significantly increased 18 F‐NaF PET uptake was observed in the subchondral bone of ACL‐reconstructed knee joints, compared with their uninjured contralateral knees . As molecular changes often precede changes at the tissue level, these findings suggest increased bone activity detected with 18 F‐NaF PET may serve as a marker for early OA in this population.…”
Section: Applications Of Pet‐mri In Nononcologic Musculoskeletal Diseasementioning
confidence: 93%